Effect Of Cold Sprayed Al Coating On Corrosion Behaviour Of Sponson Spar - Omar, Nooririnah; Mohamed, Suhana; Raja Rasi, Raja Zuraidah; Ahmad, Aminah (Penerbit Akademia Baru, 2017)

(untitled)
Aluminium types 7075 alloys are widely used in aircraft components example helicopter because of their inherent weight advantages over other metals but premature failure due to corrosion is one of the main challenges associated with this alloys, which affects the safety and readiness of aircraft. Current practise of corrosion treatment is using DOW-17process or thermal spray coating. Disadvantage of DOW-17 process it involves hazard material and thermal spray coating issue of porosity and fatigue failure. A promising coating technique cold spray, CS powder particle in supersonic jet of compressed gas impact a solid surface to cause plastic deformation without the creation of heat affected zone. Salt spray testing, SST show no rust on surface specimen of coated area and EDX result show higher weight % of Aluminium on coated area as well. Corrosion treatment is the utmost concern in the aircraft industry.